APPRAISING CAPACITY-RELATED CHALLENGES NEGATING INFRASTRUCTURE DELIVERY PERFORMANCE IN GOVERNMENT DEPARTMENTS: INSIGHTS FROM THE RESOURCE-BASED THEORY - Progress Chigangacha; Theodore Haupt; Bankole Awuzie (Journal of Construction Project Management and Innovation)
Public sector’s effort to bridge the gap between capacity demand and supply has been elusive. This challenge is glaringly noticeable especially when mega infrastructural projects are undertaken. This study uses the Value, Rarity, Imitability and Organised (VRIO) Framework to assess the human resource attributes of government departments in South Africa and how these impact on organisational performance vis-à-vis infrastructure delivery. It also proposes practical guidelines via an improvement plan developed to enhance overall organisational performance. A within-case study mixed methods research design was used. Data was elicited from a provincial government department in KwaZulu-Natal, South Africa.  Quantitative data was obtained via a structured questionnaire survey whereas qualitative data was obtained through structured interviews. The findings of the study confirm the capacity constraints prevalent within the public sector. Based on the VRIO Framework, the human resource attributes of the department were found to be valuable, and the organisation organised. However, the resources lacked the rarity and inimitability attributes. Consequently, this impacted on the department’s competitive advantage and overall performance. Furthermore, when the organisation’s performance was assessed across nine dimensions, namely; strategy, leadership, people, products, culture, technology, operations, customers and governance, culture had the lowest performance rating. Limited studies have sought to investigate the level of preparedness of public sector organisations to carry out their cardinal roles required for successful infrastructure delivery. Accordingly, this study evaluates government’s performance in public infrastructure delivery using the VRIO Framework which is underpinned by the resource-based theory (RBT).